Exploring the “faces” of Europeanization from an Albanian perspective - Irma Spahiu (Journal of Contemporary European Research, 2015)
Europeanization is a process existent in all prospective members of the European Union (EU). One such country is Albania, which has been stagnating for long in its attempts to join the EU. This commentary explores Olsen’s faces of Europeanization by observing how this process has materialized in Albanian politics and governance. It also sheds light into Europeanization approaches by studying the EU candidate countries in the Balkans aiming to look for similar or distinguishable patterns in countries where Europeanization has taken place. The commentary contends that Europeanization in Albania is occurring according to some unique features, which are labelled as ‘Europeanization by convenience’.